Development of E-Module for Learning Folklore Based on Local Wisdom - Masie, Sitti Rachmi; Malabar, Sayama; Mulyanto, Arip; Lantowa, Jafar (Journal of Ecohumanism, 2025)
This study aims to describe the development and feasibility of electronic modules based on local wisdom in learning Folklore in high schools in the Teluk Tomini area. This study uses the Research and Development (R&D) type with a 4D development model (define, design, development, and dissemination). The data collected was in the form of electronic module validation data and student responses. Experts in materials, media, language, and education practitioners carry out validation. The data collection techniques used were observation, questionnaire and interview. The data analysis used validity analysis, practicality analysis, and effectiveness analysis. The validation results show that the e-module has experienced a significant improvement after the revision. The media validation score increased from 3.63 to 4.75, while the material validation increased from 3.8 to 5 after story and media content improvements. Language validation also increased from 3.42 to 4.75, indicating that the module is easy to understand and appropriate to student development. The small and large group trials showed student responses with an average of 82.45%, which showed that this module was feasible, practical, and effective in increasing students’ motivation and cultural literacy.